Highly uniform Ni(HCO3)2 spheres: the morphology evolution and electrochemical performance. Issue 31 (27th July 2021) - Cheng, Cuixia; Chen, Fang; Yi, Huiyang; Cheng, Yinfang; Lai, Guosong
Abstract : The electrochemical performance of Nickel bicarbonate as electrode materials for lithium-ion batteries and supercapacitors could be further enhanced through rationally tuning the morphology. Abstract : Nickel bicarbonate Ni(HCO3 )2 has recently been demonstrated to be a highly attractive electrode material for lithium-ion batteries (LIBs) and supercapacitors (SCs), and its electrochemical performance could be further enhanced through rationally tuning the morphology. Herein, Ni(HCO3 )2 spheres are successfully prepared via a facile, one-step hydrothermal route. The effects of the hydrothermal duration on the phase and morphology are investigated. XRD patterns indicate a phase conversion from NiCO3 into Ni(HCO3 )2 that has never been previously reported. SEM images reveal that the reaction temperature and time play a key role in determining the phase and morphology of the resulting sample. The whole process includes, successively, nucleation, growth, self-assembly, dissolution, and recrystallization. As electrodes, the Ni(HCO3 )2 spheres reacted for 15 h, delivering 602.4 mA h g −1 after 300 cycles at 0.2 A g −1 in LIBs and a specific capacitance of 450 F g −1 after 5000 cycles at 5 A g −1 in SCs. These results show strong potential applications in energy storage devices.